Long-term fasting: Multi-system adaptations in humans (GENESIS) study–A single-arm interventional trial - Grundler, Franziska; Viallon, Magalie; Mesnage, Robin; Ruscica, Massimiliano; von Schacky, Clemens; Madeo, Frank; Hofer, Sebastian J.; Mitchell, Sarah J.; Croisille, Pierre; Wilhelmi de Toledo, Françoise (Frontiers in Nutrition, 2022)
Fasting provokes fundamental changes in the activation of metabolic and signalling pathways leading to longer and healthier lifespans in animal models. Although the involvement of different metabolites in fuelling human fasting metabolism is well known, the contribution of tissues and organs to their supply remains partly unclear. Also, changes in organ volume and composition remain relatively unexplored. Thus, processes involved in remodelling tissues during fasting and food reintroduction need to be better understood. Therefore, this study will apply state-of-the-art techniques to investigate the effects of long-term fasting and food reintroduction in humans by a multi-systemic approach focusing on changes in body composition, organ and tissue volume, lipid transport and storage, sources of protein utilization, blood metabolites, and gut microbiome profiles in a single cohort. This is a prospective, single-arm, monocentric trial. One hundred subjects will be recruited and undergo 9±3 day-long fasting periods (250 kcal/day). We will assess changes in the composition of organs, bones and blood lipid profiles before and after fasting, as well as HDL transport and storage, untargeted metabolomics of peripheral blood mononuclear cells, protein persulfidation and shotgun metagenomics of the gut microbiome. The first 32 subjects, fasting for 12 days, will be examined in more detail by magnetic resonance imaging and spectroscopy to provide quantitative information on changes in organ volume and function, followed by an additional follow-up examination after one and four months. The study protocol was approved by the ethics board of the State Medical Chamber of Baden-Württemberg on 26.07.2021 and registered at ClinicalTrials.gov (NCT05031598). The results will be disseminated through peer-reviewed publications, international conferences and social media. Trial registration: ClinicalTrials.gov Identifier: NCT05031598, September 2, 2021